USING APPROPRIATE QUESTIONING FOR INSTRUCTIONAL PURPOSE - Ariani, Sri; Susanti, Susi; Fauziah, Desna (Ensiklopedia of Journal, 2024)
The aim of this paper is to discuss the use of teacher questioning in the class. From the related literature and from the finding of several studies done by some experts, it can be concluded that teachers should ask variety of questions in their class. The questions should be the combination of high-level questions and low-level questions in order to address the different level of students’ proficiency. Asking questions properly will make them more active and confident and indirectly build their communicative competence. Teachers should also remind their students to appreciate other’s opinionsKeywords: teacher questioning, character building